The underwater soundscape in western Fram Strait: Breeding ground of Spitsbergen's endangered bowhead whales. Issue 1 (15th October 2017) - Ahonen, Heidi; Stafford, Kathleen M.; de Steur, Laura; Lydersen, Christian; Wiig, Øystein; Kovacs, Kit M.
Abstract: In the Arctic, warming and concomitant reductions in sea ice will affect the underwater soundscape, with the greatest changes likely being linked to anthropogenic activities. In this study, an acoustic recorder deployed on an oceanographic mooring in western Fram Strait documented the soundscape of this area, which is important habitat for the Critically Endangered Spitsbergen bowhead whale population. The soundscape was quasi-pristine much of the year, with low numbers of ships traversing the area. However, during summer/autumn, signals from airgun surveys were detected > 12 h/day. Mean received peak-to-peak SPLs for loud airgun pulses reached 160.46 ± 0.48 dB 1 μPa when seismic-survey ships were close (at 57 km). Bowhead whales were present almost daily October–April in all years, with singing occurring in almost every hour November–March. Currently, loud anthropogenic sound sources do not temporally overlap the peak period of bowhead singing. This study provides important baseline data for future monitoring. Highlights: At present, underwater sound levels in western Fram Strait are low to moderate (< 60 dB). Shipping activity is low, but seismic surveys occur nearby in summer/autumn. Critically endangered bowhead whales are present in the area throughout most of the year. Currently, little human activity overlaps with bowhead winter occurrence.